2011
DOI: 10.1111/j.1469-0691.2010.03410.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in nasopharyngeal bacterial carriage in preschool children from different socio-economic origins

Abstract: A prospective cohort study of preschool healthy children (3-6 years old) from two distinct socio-economic settings in the Brussels area, Belgium, was conducted during the years 2006-2008. The objectives were to evaluate nasopharyngeal colonization by Streptococcus pneumoniae, Staphylococcus aureus, Moraxella catarrhalis and Haemophilus influenzae at the time of PCV7 vaccine introduction and to assess the socio-economic level impact on flora composition and antibiotic resistance. Three hundred and thirty-three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
53
3
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 34 publications
12
53
3
2
Order By: Relevance
“…Поскольку спектр серотипов может варьировать на разных территориях страны [31, 33,34], информация об актуальном серотиповом распределении пневмокок-ка и его изменениях во времени является одним из глав-ных факторов для успешного внедрения пневмококковой вакцинации в любой стране. На современном этапе дан-ных о серотипах пневмококка в Российской Федерации мало, поскольку большинство исследований было выпол-нено 20-30 лет назад [35,36].…”
Section: циркулирующие в российской федерации серотипы S Pneumoniae unclassified
“…Поскольку спектр серотипов может варьировать на разных территориях страны [31, 33,34], информация об актуальном серотиповом распределении пневмокок-ка и его изменениях во времени является одним из глав-ных факторов для успешного внедрения пневмококковой вакцинации в любой стране. На современном этапе дан-ных о серотипах пневмококка в Российской Федерации мало, поскольку большинство исследований было выпол-нено 20-30 лет назад [35,36].…”
Section: циркулирующие в российской федерации серотипы S Pneumoniae unclassified
“…Up to 50% of children acquire S. pneumoniae in their nasopharynx at least once during the first 12 months of life. 1,2 The prevalence of S. pneumoniae increases in children during the first 24 months and then starts to decrease at 3-5 years of age. 3 It has been shown in previous studies that children who have been colonized by S. pneumoniae at early age (1-6 months) are in increased risk for developing respiratory infections and recurrent wheezing in early life and asthma in later childhood.…”
mentioning
confidence: 99%
“…It is estimated that 2 to 4 million exacerbations of COPD in the United States are attributable to M. catarrhalis infection each year (46). M. catarrhalis has been implicated in other infections, including community-acquired pneumonia (64), and extremely rarely may cause fatal bacteremia or pneumonia in patients with preexisting health conditions, such as immunodeficiency or impaired airway defenses (57).Studies show that nasopharyngeal colonization with M. catarrhalis is common in infants and young children, and a high rate of colonization is associated with an increased risk of otitis media (16,31). Recent surveys of nasopharyngeal colonization of Streptococcus pneumoniae, nontypeable Haemophilus influenzae, and M. catarrhalis showed that colonization with M. catarrhalis is highest among these pathogens surveyed in children between 2 and 12 years of age (42).…”
mentioning
confidence: 99%
“…Recent surveys of nasopharyngeal colonization of Streptococcus pneumoniae, nontypeable Haemophilus influenzae, and M. catarrhalis showed that colonization with M. catarrhalis is highest among these pathogens surveyed in children between 2 and 12 years of age (42). M. catarrhalis frequently cocolonizes human nasopharyngeal mucosal surfaces with other bacteria, including Streptococcus pneumoniae (31,42), Staphylococcus aureus (31), and H. influenzae (31,68). Efforts to identify M. catarrhalis adhesins have uncovered several bacterial surface proteins that facilitate M. catarrhalis attachment to human epithelial cells in vitro (20,27,28,36,40,41,52,54).…”
mentioning
confidence: 99%
See 1 more Smart Citation